The geometry of the SMC. - Gardiner, L. T.; Hatzidimitriou, D.; Hawkins, M. R. S. (1991)
A study is undertaken of the 3D spatial distribution of the older stellar population lying beyond about 2 kpc in projected radial distance from the center of the SMC. The study is intended to cover 120 square degrees including six overlapping Schmidt fields. The results from an area of 80 square degrees are presented including the western, northern and northeastern outer parts of the SMC.
Keywords: Astronomy; Color-Magnitude Diagram; Galactic Structure; Gravitational Fields; Luminosity; Magellanic Clouds; Spatial distribution; Star Distribution